PENGARUH MEKANISME CORPORATE GOVERNANCE DAN MANAJEMEN LABA TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2017-2020 - Aziizah Permata Ariani; Woro Utari (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to determine the effect of corporate governance mechanisms in this case is managerial ownership, earnings management is measured by discretionary accruals and financial performance conditions are measured by return on equity in banking companies in 2017-2020. The sample is 10 companies. The study used a descriptive method, with a probability sampling technique with a proposive sampling method. The results show that the corporate governance mechanism has a significant effect on earnings management. Based on the T-test partially corporate governance and earnings management have a significant effect on financial performance.